Catalyzing collective action in natural resources management - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Working with communities or groups within communities and helping them to reach their goals is a challenge. This paper provides guidelines in catalyzing collective action, especially in natural resources management, based on: the global literature on community-based management of forests and other natural resources; experience in catalyzing collective action within communities in more than 30 communities in 11 countries, using the approach called Adaptive Collaborative Management (ACM); and through experience trying to catalyze collective action in two communities in Sumatra, Indonesia.